Lightweight Design of Transmission Gear of an Aircraft Gun Ammunition Box based on SIMP Material Interpolation Model - Guanming Huang; Mingmin Liu; Hongliang Yang; Haiyang Zhang; Yongfeng Fan; Feng Xie; Shengli Ge (Jixie chuandong)
In order to enhance the performance of fighter， and realize the aim of lightweight design of aircraft gun， taking the transmission gear of a certain aircraft gun ammunition box as the research object， through topological optimization method of material interpolation model based on SIMP（solid isotropic material with realization）， a topological optimization mathematical model for the density of gear structural unit as design variable， minimum flexibility as objective function， the percentage of volume fraction before and after optimization and the structural balance equation as constraint functions is established， the topology optimization of ammunition box transmission gear is studied. Depending on the result of topology optimization， the gear structure improvement and statics analysis are carried out. The analysis results show that the optimized gear structure is reduced by 15.4%， maximum deformation is reduced by 14.2%， maximum stress is increase by 20.8%， and the gear structure lightweight design is achieved under the condition of satisfying the rigid strength of the structure and keeping the feeding principle unchanged. It has engineering application value for gear structural weight reduction， and provides the reference for other parts lightweight design.